CALCULATION METHODS OF INTERACTION OF ELECTROMAGNETIC WAVES WITH OBJECTS OF COMPLEX GEOMETRIES - MYKOLA SHOPA (TASK Quarterly, 2016)
Modeling of the electromagnetic interaction with different homogeneous or inhomogeneous objects is a fundamental and important problem. It is relatively easy to solve Maxwell equations analytically when the scattering object is spherical or cylindrical, for example. However, when it loses these properties all that is left for us is to use approximation models, to acquire the solution we need. Modeling of complex, non-spherical, asymmetric particles is used to study cosmic, cometary dust, aerosols, atmospheric pollution etc. Few analytical, surface-based and volume-based methods of light scattering modeling, most commonly used by scientists, are reviewed here.